The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1136/jcp.33.7.684
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal naphthylamidase activity as a possible aid in cytological screening.

Abstract: This is related to the nature of the cytochemical lysosomal reaction: provided that a partially hydrophilic substrate such as leucine naphthylamide (for lysosomal arylamidase activity) is used as the chromogenic substrate, the full activity of the intralysosomal enzyme in relatively normal cells will not be expressed because the lysosomal membrane will retard entry of the hydrophilic substrate to the enzyme. The activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…3) does show a wide 5ined spread of results from both these grades. As it is now ofpeaks I and 2 generally thought19 20 that perhaps no more than one ir cytological in three cases of carcinoma-in-situ may represent a condition that will progress to invasive cancer, it would be of interest to determine whether there is a rom grade V correlation between the incidence of a prominent .om benign cases): first peak and the potential to progress to invasive tional areas 'red together or cancer.…”
Section: Area Under Peaksmentioning
confidence: 99%
See 1 more Smart Citation
“…3) does show a wide 5ined spread of results from both these grades. As it is now ofpeaks I and 2 generally thought19 20 that perhaps no more than one ir cytological in three cases of carcinoma-in-situ may represent a condition that will progress to invasive cancer, it would be of interest to determine whether there is a rom grade V correlation between the incidence of a prominent .om benign cases): first peak and the potential to progress to invasive tional areas 'red together or cancer.…”
Section: Area Under Peaksmentioning
confidence: 99%
“…The first is the finding of a more labile DNA in SEM p malignant cells: this may be useful to give functional amplification in a suspect smear. The second is of 1-25 potentially more practical advantage for the auto-< 0 001 mation of cervical cancer screening.21 If the first peak [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] can, in fact, be identified in the cytologically normal 051 <0005 cells in a malignant sample, it would not be necessary 0.59 to search for the often scarce positive cells. units ± 1 25) was compared (Table 3) with the mean value for the proportional area of the apparently normal cells in the malignant, grade V samples (26'6 units ± 2-19), the difference was highly significant in the t test (p < 0001).…”
Section: Area Under Peaksmentioning
confidence: 99%
“…Although this may involve very low levels of staining, the intensity of the reaction could be enhanced considerably by using a fluorescent-Schiff reagent (Fukuda et al 1978). As regards the naphthylamidase reaction, Millett et al (1980) showed that it could be done on dried smears several days after they were prepared; its drawback was the finding of strong positive reactions in response to damage and viral infection. However, it should be pointed out (Ibrahim 1982) that neither of these procedures may be suitable for gastric smears where the pH of the gastric fluid can influence the stability both of the DNA and of the lysosomal membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Millett et al (1980) procedure was that the chromogenic substrate only weakly penetrates fully functioning lysosomal membranes so that it gives increased staining in those cells which have labile lysosomal membranes or in which the naphthylamidase activity is free from the restraint of the lysosomal membranes. It may be noted that the activity demonstrable by this test probably corresponds to that of cathepsin H. Seventy samples, from benign, preinvasive and invasive cases, were assessed by this test, the activities per cell being measured by microdensitometry.…”
Section: Proteolytic Enzymesmentioning
confidence: 99%